A Neonate with Retroperitoneal Mature Cystic Teratoma – A Case Report - Joshi, Jayateertha; Mushtaq, Owais Ahmed; Roy, Sayashi; Rao, Suchetha S (Journal of Nepal Paediatric Society, 2022)
Retroperitoneal teratoma is a rare occurrence in neonates. They are usually asymptomatic and the only finding may be abdominal distension. We report an unusual case of a large retroperitoneal teratoma in a neonate who presented with abdominal distension. Imaging done showed a cystic lesion with calcifications, internal septations and fat dense areas. It was successfully managed by surgical excision, findings of which were consistent with that of a mature cystic teratoma. Despite being rare, we must consider retroperitoneal teratomas as a differential diagnosis of an abdominal mass in a newborn. Early detection and complete surgical excision may be life-saving.